PENEGASAN BATAS KELURAHAN KAPALO KOTO DIBALAI KOTA PAYAKUMBUH DENGAN METODE KARTOMETRIK - AYU, SINDI RELA; Ramadhan, Risky (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
Abstract The aim of this research is to find out: The steps and processes in confirming the territorial boundaries of Kapalo Koto Dibalai Village based on the cartometric method. The type of research is descriptive. The research uses cartometric methods and Focus Group Discussion (FGD) to obtain information regarding the boundaries of Kapalo Koto Dibalai Village and involves community participation or what is termed the Participatory Rural Appraisal (PRA) method in the process of determining the boundaries of Kapalo Koto Dibalai Village. The research results obtained are the steps and the process of mapping the boundaries of the Kapalo Koto Dibalai Subdistrict area which is divided into 4 processes and stages, namely a. determining cartometric points. b. tracking and determining the position of boundary pillars. c. installation of boundary pillars. and d. definitive boundary map of Kapalo Koto Dibalai Village. From these 4 processes and stages, the results were obtained in the form of a Definitive Boundary Map of Kapalo Koto Dibalai Village.